Entrepreneurship Education in Business Education Programme in Tertiary Institutions in Nigeria: A Surest Way to Curb Unemployment - Atakpa, Rita Azuka; Aijene, Onoyovwi Donald (NIU Journal of Educational Research, 2025)
Entrepreneurship education is believed to be a powerful instrument that will reduce the unemployment scourgeexperienced in Nigeria today. In recent times graduates of tertiary institutions roam major cities and urban areas in search of non-existent white-collar jobs. This national economic woe is not peculiar to any particular discipline in tertiary institution in the country. In the light of this scenario the paper examined entrepreneurship education in business education programme in tertiary institutions in the country. Entrepreneurial training will expose business education students to foundation knowledge and skills required for setting up private business after graduation. Based on this fact, the paper highlights the objectives, relevance, personal characteristics of the entrepreneur, and entrepreneurship investment opportunities in business education. The paper concludes that integrating entrepreneurship training in business education programme will make the recipients to become more skilled and self -confident to start their own business. The study recommends that business education departments in all tertiary institutions in Nigeria should diversify their curriculum to give room for balanced theoretical and practical training; business education students guided on how to establish business plans and pursue goals related to entrepreneurship knowledge and skill among others. Keywords: Entrepreneurship skills, Relevance, Characteristics, unemployment, investment opportunities.